(untitled) - World Bank (Washington, D.C., 2006)
The book presents estimates of total wealth for nearly 120 countries, using economic theory to decompose the wealth of a nation into its component pieces: produced capital, natural resources and human resources. The wealth estimates provide a unique opportunity to look at economic management from a broader and comprehensive perspective. The book's basic tenet is that economic development can be conceived as a process of portfolio management, so that sustainability becomes an integral part of economic policy making.
Keywords: Sustainable development,Phát triển bền vững; Econometric models,Mô hình kinh tế